ISO 9000 And MSC Status Companies In Malaysia: Domestic And International Perspectives - Teck, Goh Eng (2001)
Companies within Malaysia's Multimedia Super Corridor were surveyed to determine current and planned levels of participation with respect to ISO 9000 standards certification, replicating earlier research that was carried out on firms in Singapore.